NMC Lithium Ion Battery Management with Distributed Monitoring Topology - Andriana, Andriana; Rahman, Sutisna Abdul; Arrazaq, Fajar (Internet of Things and Artificial Intelligence Journal, 2024)
Lithium-ion battery management often called BMS (Battery Management System) is a system that controls all operations between the battery and the required load. The advantages of lithium-ion batteries, such as high energy density and long service life, make them highly desirable. Along with the increase in demand, the use of lithium-ion batteries is also increasingly complex, such as in the use of electric vehicles and smart grids. The battery must have the same voltage as the battery when connected directly. Safety and battery life are at stake if this condition is not met. BMS is a solution to this problem. The purpose of this research is to create a BMS that has three main features: monitoring, balancing, and protection. The Nano Microcontroller can be used to build the BMS. For nickel-based battery types, namely NMC (Nickel Manganese Cobalt) batteries, the design of a battery management system with a distributed monitoring and protection architecture can help battery packs be used for various applications and reduce battery pack production costs.